POTRET PENDIDIKAN TOLERANSI DALAM MEME DI MEDIA SOSIAL SEBAGAI BAHAN LITERASI AGAMA - Ni nyoman ayu suciartini; Ni Luh PT Putriyani Dewi; Kadek Jaya Wiguna (UHN IGB Sugriwa Denpasar, 2023)
The Educational Value of Tolerance in Meme as a Media of Religious Literacy. This Currently, memes are being used as a means to voice social criticism, especially on issues that are being discussed by netizens on social media. This includes memes used as an interpretation of the meaning of religious tolerance in Indonesia. The formulation of the problem in this study is how is the portrait of religious tolerance education in memes on social media? The method used in this study is a qualitative research method with the use of semiotic studies. The elements of semiotics studied in this study are signs (images, shapes, shapes and colors), objects (meanings) and interpreters (attitudes and thought patterns of meme creators. The results of this study conclude that of the 5 memes studied, religious tolerance is in the form of creation). memes on social media are represented by the selection of characters with their respective characteristics, with different clothes as symbols or certain religious identities, differences in religious holidays that fall on the same day, different calls or greetings, are signs made by creators to give the meaning of religious tolerance education is in his meme. This viral meme which contains values of tolerance education is also effectively used as a medium or material in religious literacy.